KESIAPAN GURU TAMAN KANAK-KANAK DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA PADA PROGRAM SEKOLAH PENGGERAK - Jariyah, Ainun (Jurnal Penelitian Anak Usia Dini, 2023)
This study uses qualitative methods by collecting data through observation, document review, and interviews. The purpose of this study is to describe the readiness of Darul Mustofa Kindergarten teachers for lesson planning, teacher readiness in implementing learning activities, and teacher readiness in conducting assessments on students by implementing the independent curriculum in driving schools. The results of this study indicate that Darul Mustafa Kindergarten teachers have understood the concept of implementing the independent curriculum comprehensively. In accordance with the readiness factor of a person according to Hersey and Blanchard, Darul Mustofa Kindergarten teachers have aspects of willingness and aspects of ability in preparing teaching modules as guidelines for implementing learning activities, implementing learning activities, and assessing students.